Makna Langit dan Bumi Baru Berdasarkan Wahyu 21:1-8: Sebuah Refleksi Teologis Tentang Harapan Kekal Bagi Umat Kristiani (Jurnal Pendidikan Agama dan Teologi, 2025)
This article examines the theological meaning of the concept of the new heaven and new earth based on Revelation 21:1-8, serving as a foundation for eternal hope for Christians. Through a qualitative theological approach, this study explores how the eschatological understanding influences the faith life and spiritual attitude of believers. The concept of the new heaven and new earth not only refers to the physical renewal of the universe at the end of time but also serves as a source of spiritual strength that fosters perseverance, faith, and hope in facing worldly struggles. Furthermore, this reflection emphasizes the role of the Church as the representation of the New Jerusalem, preparing the faithful for eternal fellowship with God. Thus, the promise of renewed creation functions as an ethical and existential foundation encouraging Christians to live faithfully, courageously, and with hope until the divine promise is fully realized. This article asserts that the hope in the new heaven and new earth has tangible implications for contemporary Christian life as a reflection of the already and yet-to-be-fulfilled Kingdom of God